To evaluate the expression \( c + d \) for \( c = 6 \) and \( d = 5 \), simply substitute the values into the expression:
\[ c + d = 6 + 5 = 11 \]
So, \( c + d = 11 \).
Evaluate the expression for c = 6 and d = 5.
c + d =
11 answers
To evaluate the expression \( c + d \) for \( c = 6 \) and \( d = 5 \), simply substitute the values into the expression:
\[ c + d = 6 + 5 = 11 \]
So, \( c + d = 11 \).
To evaluate the expression \( h + j \) for \( h = 3 \) and \( j = 5 \), substitute the values into the expression:
\[ h + j = 3 + 5 = 8 \]
So, \( h + j = 8 \).
To evaluate the expression \( fg \) for \( f = 4 \) and \( g = 5 \), substitute the values into the expression:
\[ fg = 4 \times 5 = 20 \]
So, \( fg = 20 \).
To evaluate the expression \( h - j \) for \( h = -5 \) and \( j = 11 \), substitute the values into the expression:
\[ h - j = -5 - 11 \]
Calculating this gives:
\[ h - j = -5 - 11 = -16 \]
So, \( h - j = -16 \).
To evaluate the expression \( -rs \) for \( r = -6 \) and \( s = 3 \), substitute the values into the expression:
\[ -rs = -(-6)(3) \]
Calculating \( rs \):
\[ rs = (-6)(3) = -18 \]
Now, applying the negative sign:
\[ -rs = -(-18) = 18 \]
So, \( -rs = 18 \).
To evaluate the expression \( st \) for \( s = -3 \) and \( t = 6 \), substitute the values into the expression:
\[ st = (-3)(6) \]
Calculating this gives:
\[ st = -18 \]
So, \( st = -18 \).